Empagliflozin and liraglutide ameliorate HFpEF in mice via augmenting the Erbb4 signaling pathway - Ni Xia-yun; Feng Xiao-jun; Wang Zhi-hua; Zhang Yang; Little Peter J.; Cao Yang; Xu Suo-wen; Tang Li-qin; Weng Jian-ping (Acta Pharmacologica Sinica, 2024)
Heart failure with preserved ejection fraction (HFpEF) is closely associated with metabolic derangement. Sodium glucose cotransporter-2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP-1RA) exert anti-HFpEF effects, but the underlying mechanisms remain unclear. In this study, we explored the anti-HFpEF effects of empagliflozin and liraglutide and the underlying molecular mechanisms in a mouse model of HFpEF. This model was established by high-fat diet (HFD) feeding plus Nω-nitro-L-arginine methyl ester (L-NAME) treatment. The mice were treated with empagliflozin (20 mg·kg−1·d−1, i.g.) or liraglutide (0.3 mg·kg−1·d−1, i.p.) or their combination for 4 weeks. At the end of the experimental protocol, cardiac function was measured using ultrasound, then mice were euthanized and heart, liver, and kidney tissues were collected. Nuclei were isolated from frozen mouse ventricular tissue for single-nucleus RNA-sequencing (snRNA-seq). We showed that administration of empagliflozin or liraglutide alone or in combination significantly improved diastolic function, ameliorated cardiomyocyte hypertrophy and cardiac fibrosis, as well as exercise tolerance but no synergism was observed in the combination group. Furthermore, empagliflozin and/or liraglutide lowered body weight, improved glucose metabolism, lowered blood pressure, and improved liver and kidney function. After the withdrawal of empagliflozin or liraglutide for 1 week, these beneficial effects tended to diminish. The snRNA-seq analysis revealed a subcluster of myocytes, in which Erbb4 expression was down-regulated under HFpEF conditions, and restored by empagliflozin or liraglutide. Pseudo-time trajectory analysis and cell-to-cell communication studies confirmed that the Erbb4 pathway was a prominent pathway essential for both drug actions. In the HFpEF mouse model, both empagliflozin and liraglutide reversed Erbb4 down-regulation. In rat h9c2 cells, we showed that palmitic acid- or high glucose-induced changes in PKCα and/or ERK1/2 phosphorylation at least in part through Erbb4. Collectively, the single-cell atlas reveals the anti-HFpEF mechanism of empagliflozin and liraglutide, suggesting that Erbb4 pathway represents a new therapeutic target for HFpEF.